The importance of Athens and Solon, for democracy and the modern state (2019)
This article collects, due to their importance for the academy, two chapters of the research on ancientGreece, which resulted in the book: Solon and the Birth of Legislative Rationality. Here key positions arestudied to understand the importance of Athens for the world of current legal science, the importance andscope of its relationship with Greece, Rome and Sparta. Likewise, an introduction is made to Solon, as afundamental statesman in the process of expansion of Greek thought, capable of establishing, thanks to hislegislative works, the foundation of what we conceive as democracy and the modern state.They present here a culture that has been said a lot, a man about which not enough has been said. Theresearch addresses with new perspectives a thought that, although classic, does not lose its validity in the academic world to stress our current mitigation on the foundations of Western culture and thedevelopment of the first phase of the State as we currently conceive it.